Modern Problems of Tick-Borne Encephalitis Specific Prevention Communication I: Vaccinal Prevention in Area with Siberian Virus Subtype Domination - V. V. Pogodina; M. S. Shcherbinina; S. G. Gerasimov; N. M. Kolyasnikova (Эпидемиология и вакцинопрофилактика, 2015)
Tick-borne encephalitis (TBE) is a disease mainly affecting the central nervous system, serious medical and social problem in Russia and many European countries. TBE virus (TBEV) genetically divided into three major subtypes: the Far Eastern, European and Siberian. Siberian subtype of TBEV dominates in most part of Russia outside of the Far East. Modern cultural inactivated vaccine of domestic and foreign production prepared from the strains of the Far Eastern and European subtypes. In a review of the literature and our own researches are shown: the dominance of Siberian subtype (TBE) and data of vaccine-prevention. The importance of genetic differences between the Siberian subtype strains and vaccines strains are analyzed as well new approaches of the test strain selection.